O licenciamento ambiental e o desenvolvimento sistentável das cidades: o caso da Usina de Alfasto de Santarém - OLIVEIRA, Alex Ferreira de (Universidade Federal do Oeste do Pará, 2023)
The right to quality of life in cities, as one of the main elements for measuring the applicability of the concept of sustainable development to the urban environment, has been endowed with efficacy in Brazil, one of the factors that have contributed to this reality and the lack of effectiveness legal instruments that seek to promote this development. The modern national environmental law presents a series of tools to achieve this goal, which stands out as one of the most comprehensive environmental licensing. To reflect on the effectiveness of the environmental licensing as a tool for promoting sustainable development applied to cities, was used as an example the case of the asphalt plant in the neighborhood of Amparo in the city of Santarem. In order to reflect on this issue were drawn three partial objectives. Initially we identified the legitimacy of the instrument in the national environmental legislation applied to the urban environment. Since then measured the effectiveness of the instrument in the case at hand and finally analyzed the consequences of social and environmental impacts of the project and its legal repercussions. To achieve the results the research was exploratory, and its deductive method, using as references, the doctrines of urban and environmental rights and documents related to civil action from the asphalt plant. Which found that the environmental licensing case in the city, was unsuccessful in his goal of reconciling the economic and social development with the conservation of the urban environment for present and future generations.